Comparative Study of Web3D Standard Format to Determine the Base Format for A Web3D Framework - Mursid W. Hananto; Ahmad Ashari; Khabib Mustofa (IAES Indonesia Section, 2017)
With the current Web3D document format, users are forced to choose certain document formats to use, either during development with a particular tool or when it will be displayed in a browser. Only one format that can be processed by any browser at one given time. This raises the main problem of not allowing users to display a variety of objects with different formats in their browser. For this problem, a Web3D framework can be the solution, as it will provide format conversion for the browser. The conversion itself requires an appropriate base format as the conversion goal. Since there are many formats that have been implemented by users, a comparison has to be done for the purpose of choosing the suitable format. In this study, comparisons have been made to obtain some information. The information required is the complexity of each document in describing a 3D object in the browser, as well as the performance of the particular format. Web3D formats compared in this research are the standard ones: VRML and X3D. Various specific description of object formation have also been selected as sample representation for each format. Based on comparisons in the representation information of each standard format, X3D is the more suitable format for this need. As a standard format representation, the results obtained can be used for further comparisons with non-standard or proprietary formats. This information is needed to determine the final base format for the framework to be developed in subsequent research.